Chinese idioms - Petrovčič, Mateja (Acta linguistica asiatica, 2022)
Idiomatic expressions play an important role in communication. They are widely used in both spoken and written discourse and are often one of the indicatorsof native-like proficiency.This paper discussesChinese idioms chengyu in foreign language education, presentssome observations regarding the scope of idioms predictedfor the advanced level of Chinese, and introduces conceptual gaps between L1 and L2 as possible reasons for learners’ mistakenusages. This study argues thatequipping students with skills and knowledge needed forreachingcontextually appropriate useof idioms should be the main goal in the teaching/learning process and provides a set of practical suggestions as to which aspects of teaching idiomsshould be consideredthoroughly.
Keywords: besedilni korpusi; Chinese idioms; foreign language education; jezikovni prenos; kitajski pregovori; language transfer; poučevanje tujih jezikov; strategije učenja in poučevanja; teaching and learning strategies; text corpora